PENGARUH TINGKAT LITERASI BACA SISWA TERHADAP EFEKTIVITAS PEMBELAJARAN - Yudho Ramafrizal S; Teni Julia Somadi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
The title of this study is the Effect of Student Reading Literacy Level on Learning Effectiveness (Survey on Introduction of Accounting Class X Accounting at SMK Negeri 3 bandung academic year 2021-2022). This research aims to (i) find out the level of student read literacy in Introduction of Accounting of class X Accounting at SMK Negeri 3 bandung (ii) to know the level of learning effectiveness Introduction of Accounting of class X Accounting at SMK Negeri 3 bandung (iii) knowing the magnitude of the influence of students' reading literacy levels on the effectiveness of learning in Introduction of Accounting of class X Accounting at SMK Negeri 3 bandung. In this study the authors used quantitative approach methods using survey research methods, with a population of 30. To seek influence, The data analysis used is a simple linear regression analysis using IBM SPSS Statistics Version 24.0,descriptive analysis ofreading literacy level with a weight of 37.97 and an average value of 3.80, and theeffectiveness of learning with a sum weight of 40.03 and an average value of 4.00, on a simple linear regression test there is a regression coefficient value obtained is 0.580, and the determination coefficient valueis obtained the number R (correlation coefficient) or the relationship number between variable X to variable Y of 0.557 or 55.7%. The amount of contribution made by the variable level of reading literacy can be seen from the number in R Square which is 0.310 which means that the level of reading literacy affects the effectiveness of learning by 31.0%. While the other 69.0% was influenced by other factors outside of the research conducted.